AKTIVITAS ANTIINFLAMASI EKSTRAK BIJI PINANG (Areca catechu L.) MENGGUNAKAN METODE STABILITAS MEMBRAN RED BLOOD CELL (RBCs) (ANTI-INFLAMMATORY ACTIVITIES OF ARECA (Areca catechu L.) FRUIT SEED EXTRACTS USING RED BLOOD CELL (RBCs) MEMBRANE STABILITY METHOD) - Banan Fitriani; Harlia Harlia; Andi Hairil Alimuddin (Tanjungpura University, 2023)
Areca catechu L. belongs to the Arecaceae which has been widely developed as a raw material for cosmetics industries. Areca nut contains many bioactive compounds, one of which is anti-inflammatory. In this study, the anti-inflammatory activity of betel nut extract was tested using the Red Blood Cell membrane stability method. The results of phytochemical screening showed that areca nut contains flavonoid compounds. Partitioning was carried out with n-hexane, dichloromethane solvents. Partition results obtained fraction of n-hexane 1.442 g with a yield of 5.546%; fraction of dichloromethane 5.831 g with a yield of 22.427%; fraction of ethyl acetate 0.470 g with a yield of 1.807%; and fraction of methanol was 3.432 g with a yield of 13.200%. The results of the anti-inflammatory activity test showed that the highest percent value of hemolysis inhibition was in the 100 g/mL concentration of methanol extract, which was 77.693% compared to the partitioned fractions such as the n-hexane fraction 10.215%; dichloromethane fraction 75.713%; ethyl acetate fraction 73.218% and methanol fraction 48.130%. This value can be said to be good if it approaches or exceeds the positive control of diclofenac sodium, which is 89.613%. The data from this study showed that methanol extract, fraction dichloromethane and fraction ethyl acetate had the best potential as an anti-inflammatory because the percentage of hemolysis was close to positive control